A commentary on the taxonomic review of Sri Lankan Devario by Batuwita et al. 2017 (Teleostei: Danionidae) - Sudasinghe, Hiranya; Pethiyagoda, Rohan (Zootaxa, 2019)
We address several problems arising from ‘A review of the genus Devario in Sri Lanka (Teleostei: Cyprinidae), with description of two new species’, a paper authored by S. Batuwita, M. de Silva and S. Udugampola and published in 2017 in the journal FishTaxa (2(3): 156–179). The neotypes they designate for Perilampus malabaricus Jerdon and Perilampus mysoricus Jerdon are inconsistent with article 75.3 of the International Code of Zoological Nomenclature (‘the Code’) and are hence invalid. Devario udenii, which they describe as a new species, is shown to be indistinguishable from D. micronema sensu Batuwita et al. The characters by which they distinguish another new species, D. annnataliae, are shown to be self-contradictory, making it impossible to distinguish from its congeners; it is treated as a species inquirendum. The diagnoses provided for D. malabaricus, D. micronema and D. monticola are ambiguous and self-contradictory, rendering them unusable. Much of the material examined, stated to be in the collection of the National Museum of Sri Lanka, is not deposited in that institution: such material as is deposited is inconsistent with the specimen data published by Batuwita et al.